Alih Kode dan Campur Kode dalam Interaksi Digital Generasi Z Indonesia: Kajian Sosiolinguistik pada Media Sosial Instagram - Muhammad Nurahmad; Nurasia Natsir (Universitas Palan, 2026)
This study examines the phenomena of code-switching and code-mixing in the digital interactions of Indonesian Generation Z on Instagram. Using a sociolinguistic approach with virtual ethnography, data were collected from 1,200 posts and comments published between January and June 2024, complemented by in-depth interviews to explore the factors influencing language choice. The findings reveal that code-switching occurred in 68.4% of the data, with intrasentential switching as the dominant pattern (47.3%), followed by intersentential switching (38.6%) and external switching (14.1%), indicating Generation Z’s high multilingual competence. Code-mixing appeared in 82.1% of the data, primarily through the insertion of English vocabulary into Indonesian (63.2%), followed by regional languages such as Javanese, Sundanese, and Betawi (27.1%), particularly in nostalgic, culinary, and emotionally expressive content. The main factors influencing these practices include social identity, community affiliation, communicative efficiency, emotional expression, and audience context. The study concludes that code-switching and code-mixing function as deliberate communicative strategies that reflect Generation Z’s hybrid identity in digital spaces, offering important implications for digital sociolinguistics, language education, language policy, and digital content development.